Efficacy and Safety of Generic Sofosbuvir Plus Daclatasvir and Sofosbuvir/Velpatasvir in HCV Genotype 3-Infected Patients: Real-World Outcomes From Pakistan - Mushtaq, Saima; Akhter, Tayyab Saeed; Khan, Amjad; Sohail, Aamir; Khan, Arshad; Manzoor, Sobia (Frontiers in Pharmacology, 2020)
The real-world effectiveness of direct-acting antivirals (DAAs) in the form of comparing the sustained virological response (SVR) of sofosbuvir +daclatasvir ± ribavirin and sofosbuvir/velpatasvir ± ribavirin informs better treatment decisions. To assess the efficacy and safety of SOF + DCV ± RBV and SOF/VEL ± RBV in treating patients with HCV genotype 3 patients. Observational, intent-to-treat cohort of chronic HCV patients initiated generic SOF + DCV ± RBV or SOF/VEL ± RBV at government and private hospitals under the national hepatitis C program of Pakistan. Out of 1388 patients, 70% of patients received SOF + DCV in government hospitals and 30% received SOF/VEL in private hospitals. The overall SVR12 rate was 95.5 %. Moreover, SVR rates were comparable between SOF + DCV (94.4%) and SOF/VEL (94.7%). Primary nonresponse occurred slightly more among those treated with SOF-DCV than SOF-VEL (4.1% vs 3.8%, P = .05). In multivariate models, the significant predictors of non-SVR were age greater than 60 years (odds ratio [OR] 4.46; 95% CI, 2.35-8.46, P = <.001) and history of advance liver disease (OR 53.91; 95% CI, 26.49-109.6, P = <.001). Skin rash (51% vs 44%) and oral ulcers (45% vs 40%) were high in patients taking SOF-DCV then SOF-VEL. Generic SOF + DCV ± RBV or SOF/VEL ± RBV achieved equally high SVR12 rates and was well tolerated in a diverse cohort of patients with advance liver disease.